PENERAPAN ASAS KESEPAKATAN DALAM PENGADAAN TANAH BAGI PEMBANGUNAN UNTUK KEPENTINGAN UMUM - Djoni Sumardi Gozali (Universitas Airlangga, 2017)
The legal issues of this research consist of the application of the consensualism principle in land procurement for development for the sake of public interest. The method of this research is normative legal research by applying statute approach, conceptual approach.The results of this research there is deviation in the enforcement of the consensualism principle in Article 66 paragraph 4 of Act Number 2 of 2012 which determines that deliberation towards consensus isn only in a form of compensation, is contrary to Article 37 paragraph 1 and 2 of Act Number 2 of 2012 which stipulates that deliberation is conducted in determining the form and/or the amount of compensation. The provision of Article 42 of Law Number 2 Year 2012 which determines the reason for consignment or care for compensation in a State court shall be done if the entitled to be denied the form and / or amount of compensation, replace with the principle of agreement because it is done without based on the agreement of the parties, With the essence of deliberation that requires an agreement.